Single-cell sequencing in non-obstructive azoospermia: insights from primary and re-analysis studies - Jiang, Zesong; Zhang, Junwen; Qiu, Zhongjian; Zhang, Yufei; Li, Nan; Hu, Jianmeng; Zhu, Zhiguo (Frontiers in Endocrinology, 2025)
Non-obstructive azoospermia (NOA) constitutes one of the most severe forms of male infertility. Recent advancements in single-cell sequencing have significantly contributed to understanding the molecular landscape of NOA in human testicular tissues, elucidating the factors that underpin spermatogenic dysfunction. This technology has improved our understanding of the condition at a cellular level. Concurrently, bioinformatics developments have facilitated the re-analysis of publicly available single-cell datasets, offering novel insights into the disorder. Nevertheless, a comprehensive review integrating primary and re-analysis studies of single-cell sequencing in NOA is lacking. This review systematically evaluates 10 primary studies reporting original single-cell sequencing data of human NOA testicular samples and 22 secondary studies that re-analyzed these published data. We explore single-cell sequencing applications in germ cells, Sertoli cells, and Leydig cells, offering a comprehensive overview of molecular insights into spermatogenic dysfunction. Our review highlights novel findings in secondary studies, including the roles of transcriptional regulators, RNA transcription, endocrine disruptors, and microtubular cytoskeleton, thereby bridging primary studies and re-analysis studies. Additionally, we discussed future research directions and the challenges of translating single-cell research findings into clinical applications. In summary, single-cell sequencing offers a high-resolution, single-cell perspective of NOA testicular tissue, paving the way for innovative therapeutic strategies in male infertility.